2019
DOI: 10.1111/bjh.16168
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib monotherapy outside of clinical trial setting in Waldenström macroglobulinaemia: practice patterns, toxicities and outcomes

Abstract: Ibrutinib-related data in Waldenstr€ om macroglobulinaemia (WM) remain sparse, particularly outside of trials. We report on 80 patients [previously treated, n = 67 (84%), treatment-na€ ıve, n = 13 (16%)] with WM, evaluated consecutively at Mayo Clinic, who received ibrutinib off-study after its approval in 2015 for WM. Overall response rate (ORR) was 91%; major-response rate (MRR) was 78%. The median time to first response and best response was 2Á9 [95% confidence interval (CI): 2-4] and 5Á7 (95% CI: 4-12) mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
5
33
0
Order By: Relevance
“…Differences in overall survival or survival after first treatment initiation were not assessed due to a small number of deaths in this cohort (n = 37; 13%) at the time of this report. Calculations were obtained using STATA 15…”
Section: Discussionmentioning
confidence: 99%
“…Differences in overall survival or survival after first treatment initiation were not assessed due to a small number of deaths in this cohort (n = 37; 13%) at the time of this report. Calculations were obtained using STATA 15…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation was seen in 11%. The IgM rebound was seen in 36% of patients following ibrutinib discontinuation 138,139 …”
Section: Managementmentioning
confidence: 99%
“…The differential effect of ibrutinib on the molecular subtypes of WM has been striking: 100% of MYD88 L265P, CXCR4 WT patients responded to ibrutinib, compared to 85.7% and 60% of patients in the double mutant and double WT groups respectively [ 110 ]. In a retrospective analysis of WM patients treated with ibrutinib, Abeykoon et al [ 111 ] reported on five MYD88 WT patients, among whom two achieved a partial response, one achieved a minor response, and the other did not respond [ 111 ]. These data indicate the potential for use of MYD88 mutation status as a biomarker for response to BTK inhibition.…”
Section: Future Directionsmentioning
confidence: 99%